Unlocked versus dynamic and static distal locked femoral nails in stable and unstable intertrochanteric fractures. A prospective study. (November 2018) - Ciaffa, V.; Vicenti, G.; Mori, C.M.; Panella, A.; Conserva, V.; Corina, G.; Scialpi, L.; Speciale, M.; Fraccascia, A.; Picca, G.; Carrozzo, M.; Leone, A.; et al.
Abstract: Introduction: Few clinical studies have analyzed the utility of distal interlocking screws in stable and unstable intertrochanteric fractures treated with intramedullary devices. We performed a prospective analysis comparing short unlocked versus short dynamic and short static distal locked intramedullary nails. Materials and methods: Nine level-II trauma centres were involved in the study. 240 patients over the age of 65 with a stable (AO/OTA 31-A1) or unstable intertrochanteric fracture (AO/OTA 31-A2) were prospectively investigated. The same type of nail was used in every patient. Patients were randomly divided into 3 groups according to the type of distal locking used. Intra-operative variables were examined and patients were followed clinically and radiographically at 1, 3, 6, 12 months postoperatively. All complications were recorded. Results: A total of 212 patients completed 1 year of follow-up visits. In the Unlocking Group (UG) the operation time, blood loss, fluoroscopy time, total length of incision were significantly decreased compared to both the Dynamic Group (DG) and the Static Group (SG) (p < 0.05). Conversely, no reliable differences in intraoperative variables were noted between the Dynamic Group and the Static Group (p > 0.05). In terms of time of fracture union we found no differences among the three Groups (p > 0.05). Moreover, no cases of limb shortening >1 cm or varus collapse were detected in any group. The 3 Groups were similar in terms of HHS, SF-12 and Barthel index results at 1-year follow-up (p > 0.05). Finally, no significant differences were demonstrated across the three Groups in terms of major complications. Conclusions: This clinical study further confirms the hypothesis that short intramedullary nails do not need to be locked for stable and unstable intertrochanteric fractures.